IN VITRO FERTILIZATION OF BUFFALO OOCYTES MATURED IN VITRO IN THREE DIFFERENT MEDIA - RUHIL, SWATI; PUROHIT, G N; PUROHIT, G N (The Indian Journal of Animal Reproduction, 2023)
In order to evaluate the effect of media on in vitro maturation (IVM; 24 hours) and subsequent fertilization (IVF; 24 hours), culturable grade buffalo oocytes (n=1058) were matured (Expt. 1, n=517) or matured and fertilized (Expt. 2, n=541) in vitro in three different media (Ham’s F-10, Waymouth MB and TCM-199) with same supplements (5μg/ml FSH, 5μg/ml LH, 1 μg/ml estradiol, 25mMHepes, 0.25mMpyruvate and antibiotics) to record two end points; IVM and IVF. The overall mean culturable grade oocyte recovery was 3.12±0.20. At the end of Expt. 1 significantly higher (P<0.01) proportion of oocytes were matured in vitro in Waymouth compared to Ham’s F-10. In TCM-199, IVM rates were non-significantly higher compared to Ham’s F-10 and non-significantly lower compared to Waymouth MB medium. At the end of Expt. 2 the proportion of oocytes that fertilized were 10%, 17% and 16.4% in Ham’s F-10, Waymouth and TCM-199 respectively which were non significantly different It was concluded that Way mouth MB medium is the most appropriate medium for in vitro maturation of buffalo oocytes followed by TCM-199 and Ham’s F 10 however the IVM media had a negligible effect on the subsequent fertilization of buffalo oocytes